2000
DOI: 10.1007/s004019900170
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological analysis of four autopsy cases of HTLV-I-associated myelopathy/tropical spastic paraparesis: inflammatory changes occur simultaneously in the entire central nervous system

Abstract: Although brain lesions have been described in some cases with HTLV-I-associated myelopathy/tropical spastic paraparesis (HAM/TSP), little is known about the nature of brain lesion and its relation to the spinal cord lesion. In the present study, we performed histopathological analysis of the brain and the spinal cord of four autopsied cases with HAM/TSP to clarify the relationship between the brain and the spinal cord lesions. In two cases with active-chronic inflammation in the spinal cord, perivascular infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 22 publications
4
56
1
Order By: Relevance
“…Cerebral atrophy was observed in 14% of our patients with HAM/TSP. In the study by Griffith et the mechanisms of brain atrophy are the same responsible for spinal cord atrophy secondary to degeneration of the parenchyma 26 . Cervilla et al did not show hyperintense lesions in the spinal cord of patients with HAM/TSP, but 87% had atrophy of the dorsal segment 18 .…”
Section: Discussionmentioning
confidence: 98%
“…Cerebral atrophy was observed in 14% of our patients with HAM/TSP. In the study by Griffith et the mechanisms of brain atrophy are the same responsible for spinal cord atrophy secondary to degeneration of the parenchyma 26 . Cervilla et al did not show hyperintense lesions in the spinal cord of patients with HAM/TSP, but 87% had atrophy of the dorsal segment 18 .…”
Section: Discussionmentioning
confidence: 98%
“…Others suggested that the involvement of posterior and lateral columns is an independent degenerative process. We would favor the first hypotheses because it has been demonstrated, in recent neuropathological research that the entire CNS is affected simultaneously 46,52 . Thus, the lack of correlation between CMCT obtained by TMS and somatosensory evoked potentials, in some groups of patients, could be due more to disease duration than the anatomical distribution of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…The autopsied cases of long evolution are very few in the literature 8,[10][11][12]15,17 . The two Iwasaki's 8 cases of long evolution (19 and 28 years, respectively) were typical clinical TSP/HAM and, neuropathologically, "neither lymphocytic nor monocytic cell infiltration was seen in markedly devastated and shrunken parenchymal tissues".…”
Section: Discussionmentioning
confidence: 99%
“…Peripherally, the spinal ganglia exhibited slight lymphocytic infiltration, and the peripheral nerves and muscles were normal. Aye et al 17 analyzed four cases with, respectively, 7, 9, 15 and 24 years of illness duration, with incapacitating clinical signs in the three first ones, without, however, clinical cerebral signs. Their long evolutive cases (15 and 24 years, respectively) had degeneration of the lateral corticospinal tract and of the spinocerebellar or spinothalamic tracts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation